Study of turbomachinery flows using open source analysis software - Çetin, Büşra (Graduate School, 2022)
Construction of a proper mesh is a crucial stage of computational studies to obtain acceptable results as the quality of the mesh specifies accuracy, convergence and computational time. Solution is mainly restricted by imperfections on the geometry definition, low mesh quality and relatively coarse mesh structure. OpenFOAM as an open source software, which offers tools to generate grids for the solution domain in addition to execute CFD analysis. For complex geometries, mesh can be constructed by snappyHexMesh utility of OpenFOAM. snappyHexMesh creates an unstructured mesh over a structured state that is generated by blockMesh utility thus it presents an automatic mesh construction tool for engineering applications. In this study, NASA Rotor 37 that is an axial flow, transonic compressor delivering a pressure ratio of 2.1 at design conditions, is analyzed. OpenFOAM was used for both mesh construction and CFD analysis. An unstructured mesh was generated by snappyHexMesh. Since the solution domain contains periodic boundaries, cyclic boundary condition was used. Generation of cyclic BCs on an unstructured mesh are a difficult process by an open source tool as two periodic boundaries must be identical in order to overlap grids on these boundaries. The cyclic surfaces were produced as circular patterns of each other. Quality of the geometry file is also an important factor for mesh construction. Because of unstructured results of snappyHexMesh with non conformal grids, cyclic boundary condition option could not be used solitarily. Non conformal periodic boundaries are matched by cyclicAMI boundary condition options of OpenFOAM that states Arbitrary Mesh Interface and contructs the mesh matching for non overlapping grids. Integration of cyclicAMI was applied by an exclusive OpenFOAM dictionary, createPatchDict. Thus, for obtaining a mesh automatically, geometry files must have high quality, and periodic boundaries must be geometrically identical. Flow field of the rotor was evaluated in terms of total pressure and temperature ratios, and Mach number distributions. Spalart-Allmaras turbulence model was used. Computational results were compared with experimental measurements and other computational results. According to the results, method of preparation of the geometry and construction of the mesh affect accuracy considerably. Total temperature and pressure under predicted in comparison to experiment and other computational studies. It may be caused by rhoSimpleFoam that cannot capture shock, or by low quality geometry. Hence a proper solver and high quality geometry can give satisfying results.
Açık kaynaklı analiz yazılımı kullanarak turbomakine akışlarının incelenmesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: turbomakine akışları; turbomachinery flows; open source; açık kaynak